Design of anchor reinforcement for seismic tension loads. (1st June 2018) - Petersen, Derek; Lin, Zhibin; Zhao, Jian
Abstract: This paper presents a study of cast-in anchors in reinforced concrete subjected to both monotonic and cyclic tension. Laboratory tests using 25 mm [1 in.] diameter anchor bolts showed that the code-conforming anchor reinforcement may not ensure anchor steel failure though it effectively prevented concrete breakout. Based on the observations and other tests in the literature, recommendations for the design of anchor tension reinforcement were proposed, which consists of (1) load-carrying reinforcement in the direction of the anchors; (2) crack-controlling reinforcement in all directions that have a limited edge distance; and (3) local confining reinforcement near the anchor head if side-face blowout may control the failure. The proposed anchor reinforcement was proven effective using additional laboratory tests. Further studies are needed to verify the reinforcement design for anchor connections.